2015
DOI: 10.1007/s11999-014-3685-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Potential Malnutrition Associated With Septic Failure and Acute Infection After Revision Total Joint Arthroplasty?

Abstract: Level III, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 32 publications
2
70
0
1
Order By: Relevance
“…Other complications associated with malnutrition in patients undergoing orthopaedic surgery include postoperative hematoma formation, and renal, cardiovascular, and neurovascular complications [7]. Results of our study are consistent with those of other studies showing an association between low serum albumin and an increase in multiple major perioperative complications [5,12,27,32] To our knowledge, our study is the largest to date evaluating the independent association between low serum albumin and perioperative complications after TKA. We focused specifically on elective primary TKAs and provide a detailed analysis of specific complications which are increased in patients with low serum albumin.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Other complications associated with malnutrition in patients undergoing orthopaedic surgery include postoperative hematoma formation, and renal, cardiovascular, and neurovascular complications [7]. Results of our study are consistent with those of other studies showing an association between low serum albumin and an increase in multiple major perioperative complications [5,12,27,32] To our knowledge, our study is the largest to date evaluating the independent association between low serum albumin and perioperative complications after TKA. We focused specifically on elective primary TKAs and provide a detailed analysis of specific complications which are increased in patients with low serum albumin.…”
Section: Discussionsupporting
confidence: 89%
“…Malnutrition has been linked to persistent wound drainage, failure of wound healing, and surgical site infections after joint arthroplasty [5,9,11,15]. Deep periprosthetic infections (acute and chronic) also have been reported at a higher rate in patients with malnutrition [32]. Some studies have concluded that patients with malnutrition had a longer postoperative length of stay [12,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sample size is likely underpowered to detect more predictors of PJI. This does, however, raise the concern that there may exist some underlying predisposition to infection in this cohort that may not be readily detected that may include subclinical immune deficiencies or malnutrition [10].…”
Section: Discussionmentioning
confidence: 86%
“…Patients with a history of PJI had a greater risk of developing PJI in a subsequent THA or TKA (10 Table 2). …”
Section: Resultsmentioning
confidence: 99%